Traces of dietary patterns in saliva of hominids: Profiling salivary amino acid fingerprints in great apes and humans. Issue 175 (February 2023) - Richter, Carolin; Behringer, Verena; Manig, Friederike; Henle, Thomas; Hohmann, Gottfried; Zierau, Oliver
Abstract: Herbivorous animals that regularly consume tannin-rich food are known to secrete certain tannin-binding salivary proteins (TBSPs), especially proline-rich proteins and histidine-rich proteins, as an effective measure to counteract the antinutritive effects of dietary tannins. Due to their high binding capacity, TBSPs complex with tannins in the oral cavity, and thereby protect dietary proteins and digestive enzymes. Although the natural diet of great apes (Hominidae) is biased toward ripe fruits, analyses of food plants revealed that their natural diet contains considerable amounts of tannins, which is raising the question of possible counter-measures to cope with dietary tannins. In our study, we investigated the salivary amino acid profiles of zoo-housed Pan paniscus, Pan troglodytes, Gorilla gorilla, and Pongo abelii, and compared their results with corresponding data from Homo sapiens . Individual saliva samples of 42 apes and 17 humans were collected and quantitated by amino acid analysis, using cation-exchange chromatography with postcolumn derivatization, following acid hydrolysis. We found species-specific differences in the salivary amino acid profiles with average total salivary protein concentration ranging from 308.8 mg/dL in Po. abelii to 1165.6 mg/dL in G. gorilla . Total salivary protein was consistently higher in ape than in human saliva samples (174 mg/dL). All apes had on average also higher relative proline levels than humans did. Histidine levels had the highest concentration in the samples from Po. abelii followed by P. paniscus . In all ape species, the high salivary concentrations of proline and histidine are considered to be indicative of high concentrations of TBSPs in hominids. Given that the species differences in salivary composition obtained in this study correspond with overall patterns of secondary compound content in the diet of wild populations, we assume that salivary composition is resilient to acute and long-lasting changes in diet composition in general and tannin content in particular.